Thermal modelling and characteristic evaluation of electric vehicle battery system. (August 2021) - Afzal, Asif; Kaladgi, Abdul Razak; Jilte, R.D.; Ibrahim, Muhammad; Kumar, Rahul; Mujtaba, M.A.; Alshahrani, Saad; Saleel, C. Ahamed
Abstract: Thermal modelling of Li-ion battery system used in electric/hybrid electric vehicles is carried out. The main highlight of this study is the numerical modelling of Li-ion battery using finite volume method with the adoption of realistic coupled heat and fluid flow process. Thermal characters of the battery system are analyzed with the change in parameters like flow Reynolds number, battery internal heat generation, the length to width ratio, and the conduction-convection related parameter at the interface of battery and air. In detail analysis of maximum temperature, heat flux variations, Nusselt number, friction coefficient, coolant temperature, and velocity distributions are carried out. Finally, the effect of channel width formed between two parallel placed battery cells is also carried. The numerical analysis performed reveals that the length to width ratio of battery does not impact the thermal performance of battery. At lower Reynolds number, the conduction-convection parameter plays a significant role in reduction of battery temperature avoiding thermal stresses developed. Channel spacing has a prominent role in variation of battery and coolant temperature. The battery surface temperature is largely affected by parameters considered. However, it is at higher input of conduction-convection parameter, Reynolds number, and channel spacing the thermal variation remains insignificant.